Defining pain-validation: The importance of validation in reducing the stresses of chronic pain - Nicola, Melinda; Correia, Helen; Ditchburn, Graeme; Drummond, Peter D. (Frontiers in Pain Research, 2022)
Purpose To validate an individual's feelings or behaviour is to sanction their thoughts or actions as worthy of social acceptance and support. In contrast, rejection of the individual's communicated experience indicates a denial of social acceptance, representing a potential survival threat. Pain-invalidation, though ill-defined, appears to be a fundamental component of psychosocial stress for people with chronic pain. As such, the aim of this paper was to define pain-validation and outline its importance for those with chronic pain. Methods The pain-validation construct was defined using themes inherent in the narratives of those with chronic pain, as identified in a previously published systematic search and thematic analysis, together with examination of additional literature on pain-validation in the clinical context. Results We present a construct definition, proposing that pain-validation must necessarily include: (i) belief that the pain experience is true for the individual, (ii) acceptability of the individual's expressions of pain, and (iii) communication of belief and acceptability to the individual experiencing pain. Further, we outline the importance of pain-validation as a protective factor and means of reducing many of the psychosocial stresses of chronic pain; for example, by indicating social support for pain-coping, buffering negative emotions, and re-enforcing unity and shared identity. Implications The role of pain-validation in the current era of pain management intervention is discussed. Adhering to interventions that involve cognitive and behavioural change is often difficult. Acknowledging and validating the acceptability of the patient's pain experience in the early stages of pain management may, therefore, be a key component of intervention that encourages compliance to the treatment plan and achieving therapeutic goals.